Calvinism and culture - Graham, Gordon (The Kuyper Center review, 2013)
Culture regained? On the impossibility and meaninglessness of culture in (some) Calvinist thought Neal DeRoo -- Reply to Neal DeRoo Albert M. Wolters -- The pilgrimage to Kuyper? Adolf Schlatter and Abraham Kuyper on theology, culture, and art Michael Bräutigam -- Theology and architecture : Calvinist principles for the faithful construction of urban space Matthew Kaemingk -- Calvinism, necessity, and the death of tragedy John de Soto -- The correlation between creation and culture in the theology of Abraham Kuyper and Colin E. Gunton William Baltmanis Whitney -- The Calvinian eucharistic poetics of Emily Dickinson Jennifer Wang -- Beautiful harmony : Kuyper, Dooyeweerd, and the American musical avant-garde Janet Danielson -- From neo-Calvinism to Broadway boogie woogie : Abraham Kuyper as the jilted stepfather of Piet Mondrian James D.Bratt -- The music God likes and the Calvinist tradition John Barber -- The vampire squid : Abraham Kuyper on public entertainment Clifford B. Anderson -- To transcend and to transform : the neo-Calvinist relationship of church and cultural transformation James Eglinton